Infarction of left upper pulmonary lobe after patent ductus arteriosus surgery in a preterm neonate - Filomena Valentina Paradiso; Elena Jane Mason; Riccardo Marano; Lorenzo Nanni (Elsevier, 2016)
Patent ductus arteriosus (PDA) in preterm babies is common and related to high morbidity and mortality if left untreated. Although its optimal management is still debated, surgical ligation or clipping remain the only available options for pharmacologically unresponsive PDAs. The surgical procedure adds its own risk to this fragile population. We report the first case of premature neonate with a left upper pulmonary lobe venous infarction, following PDA ligation.